Demographic senescence and effects on population dynamics of a perennial plant. Issue 8 (13th May 2019) - Edelfeldt, Stina; Bengtsson, Karin; Dahlgren, Johan P.
Abstract: Demographic rates in plants are usually assumed to be more stage or size dependent than age dependent, and aging is therefore not considered in demographic models. However, little is known about the effect of age on demographic rates, as there still are few studies based on long‐term individual‐based plant population data that consider both individual age and size. In addition, little is known about how aging of individuals may affect population dynamics. We present analyses of demographic data for three populations of Fumana procumbens collected 1985–2013, on individuals with known year of germination. We modeled age‐ and size‐dependence of the vital rates of survival, growth, fruiting probability, and fruit number using thin plate spline regressions, and constructed an age × size integral projection model (IPM) to project population‐level effects of aging. We found strong correlations between age and vital rates in solely age‐based vital rate models, where vital rates initially increased with age, after which they stabilized and, in some cases, eventually declined. In survival models with both age and size, the effects of age were statistically significant, whereas size effects were insignificant at two of the sites. For other vital rates, most of the effect of age could be explained by size alone. In addition, including the age effects on survival in the IPM led to lower population growth rates compared to predictions of a size‐only IPM. These results illustrate that demographic senescence does occur in perennial plants, which has only been demonstrated clearly in a few recent detailed studies. Moreover, we show that population projections may be overly optimistic if they do not consider plant age. We conclude that the possibility of demographic senescence should be considered in demographic population models, such as those used in viability analyses of threatened species.